2018
DOI: 10.21608/ejnf.2018.75774
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Growth, Carcass Characteristic, Digestion, Caecal Fermentation, Microflora, and Some Blood Biochemical Components Affected by Oral Administration of Anaerobic Probiotic (Zad®)

Abstract: he current research designed to study the influences of diverse doses of oral administration of anaerobic probiotic (ZAD®) on growth performance, carcass characteristic, digestibility coefficient, caecal activity, microflora and some blood biochemical components of growing rabbits. At 6 weeks (average body weight 539.87±13.35 g), one hundred and eighty weaned male rabbits from New Zealand White (NZW) were randomly distributed to four groups. The control group received orally 0.0 ZAD ® ; the experimental groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…The results reported by Mohamed et al [ 27 ] partially agreed with the abovementioned, as no significant effect was reported on globulin, while a significant increase in WBC and total protein in growing rabbits fed with diets supplemented with Lactobacillus acidophilus were observed. An increase of total protein along with an increase in globulins was observed by other authors [ 25 , 41 ]. Fathi et al [ 25 ], in local breed growing rabbits fed with two different doses of probiotic containing Bacillus subtilis , reported a slight increase of total protein level and a similar trend in globulins with the highest dose of probiotic.…”
Section: Effects Of Probiotics On Rabbitssupporting
confidence: 73%
See 2 more Smart Citations
“…The results reported by Mohamed et al [ 27 ] partially agreed with the abovementioned, as no significant effect was reported on globulin, while a significant increase in WBC and total protein in growing rabbits fed with diets supplemented with Lactobacillus acidophilus were observed. An increase of total protein along with an increase in globulins was observed by other authors [ 25 , 41 ]. Fathi et al [ 25 ], in local breed growing rabbits fed with two different doses of probiotic containing Bacillus subtilis , reported a slight increase of total protein level and a similar trend in globulins with the highest dose of probiotic.…”
Section: Effects Of Probiotics On Rabbitssupporting
confidence: 73%
“…An increment in lactobacilli, due to probiotic diets, was also reported by Shen et al [ 35 ] and Abdel-Azeem et al [ 41 ]. New Zealand White rabbits were fed Lactobacillus casei RABX1 (accession number: KT944253) resuspended in the milk (5–6 × 10 8 CFU/mL) and orally administered from 5 to 13 days of age.…”
Section: Effects Of Probiotics On Rabbitssupporting
confidence: 69%
See 1 more Smart Citation
“…Second, it can be related to the increase in the level of globulins, which constitutes a fraction of serum proteins, indicating a possible improvement in the immunity of rabbits, in particular when Saccharomyces boulardii CNCM I-745 is used [ 45 ]. Regarding albumin, which is the main protein component of serum, this fraction can exert an effect on the humoral response and is likely to support the increase in immune organs after probiotic treatment [ 46 , 47 ]. The sex effect observed for these two parameters, mainly with higher amounts for males compared to females, is in contrast to those reported in the literature [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are overall in accordance with those of earlier studies [85][86][87], who reported that the levels of total serum proteins, albumin, globulin and AP, of rabbits given probiotics were not affected. In a similar experimental design to our trial, a study [88] reported non-significant results in the levels of creatinine in New Zealand rabbits that consumed multiple doses of anaerobic probiotics during a period of 56 days. On the other hand, the rabbits of our trial did not exhibit liver damage, because none of the blood metabolites were altered among the groups that received the probiotics.…”
Section: Creatinine Alb Pt Asat Alat and Ap In Experimentsmentioning
confidence: 87%